2009
DOI: 10.1016/j.polymdegradstab.2009.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Layered double hydroxides intercalated with borate anions: Fire and thermal properties in ethylene vinyl acetate copolymer

Abstract: This paper is NOT THE PUBLISHED VERSION; but the author's final, peer-reviewed manuscript. The published version may be accessed by following the link in th citation below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 31 publications
3
41
0
Order By: Relevance
“…10 Recently, simple LDHs containing inorganic anions have been employed as inorganic UV blocking materials for the protection of asphalt and rubber against UV aging. LDHs are a class of anionic clays 7 which have received much attention from both the chemical industry and academia in view of their actual and potential applications in catalysis, 8 electrode materials 9 and polymer additives.…”
Section: Introductionmentioning
confidence: 99%
“…10 Recently, simple LDHs containing inorganic anions have been employed as inorganic UV blocking materials for the protection of asphalt and rubber against UV aging. LDHs are a class of anionic clays 7 which have received much attention from both the chemical industry and academia in view of their actual and potential applications in catalysis, 8 electrode materials 9 and polymer additives.…”
Section: Introductionmentioning
confidence: 99%
“…LDHs with intercalated borate anions were also found to be better flame retardants in EVA when compared to conventional flame retardant fillers such as ATH, MH, or zinc hydroxide (ZH). Nyambo and Wilkie [15] found that at 40 wt% loading, borate-intercalated Mg/Al and Zn/Al LDHs showed a significantly higher reduction of the PHRR (74% and 77%) in EVA/LDH composites than those consisting of ZH (47%), MH (65%), and their combinations. However, at similar loadings, ATH and zinc borate resulted in a higher reduction in the PHRR (89%) when compared to that of LDHs (Table 2).…”
Section: Flame Retardancy Of Ldhs In Ethyleneevinyl Acetate Copolymersmentioning
confidence: 99%
“…Cone Calorimeter Data[15] for Ethylene Vinyl Acetate Composites Obtained at an Incident Heat Flux of 35 kW m À2…”
mentioning
confidence: 99%
“…Initially there is a release of acetic acid gas caused by the deacetylation followed by the production of a wide range of products such as hydroxyl or hydroperoxides, a mixture of carbonyl products (ketones and α , β ‐unsaturated groups), lactones, and a mixture of substituted vinyl products . Inorganic fillers that were said to improve the flame retardancy of EVA copolymers include metal hydroxides (Mg(OH) 2 and Al(OH) 3 ), mixtures of ammonium polyphosphate, pentaerythritol, and melamine .…”
Section: Introductionmentioning
confidence: 99%